Consumer Information and Price Transmission: Empirical Evidence - Jens-Peter Loy; Dieter Pennerstorfer; Daniela Rroshi; Christoph Weiss; Biliana Yontcheva (The Journal of Industrial Economics, 2022)
We investigate how consumer information affects price adjustment in the Austrian retail gasoline market. Our measure of consumer information is obtained from detailed census data on commuting behavior, as commuters can freely sample prices on their commuting route and are thus better informed about prices. A threshold error-correction model suggests that prices adjust more quickly if cost shocks exceed certain thresholds. Parametric and semi-parametric regressions show that a larger share of informed consumers increases both transmission speed and pass-through rate, but has no effect on the asymmetry of cost transmission.
Keywords: 330